Laparoscopic colposuspension for urinary incontinence in women - Dean, Nicola (Cochrane Database Syst Rev, 2017)
BACKGROUND: Stress urinary incontinence (SUI) imposes significant health and economic burden on society and the women affected. Laparoscopic colposuspension was one of the first minimal access operations for the treatment of women with SUI, with the presumed advantages of avoiding major incisions, shorter hospital stays and quicker return to normal activities. OBJECTIVES: To determine the effects of laparoscopic colposuspension for urinary incontinence in women. SEARCH METHODS: We searched the Cochrane Incontinence Group Trials Register (searched 2 July 2009), and sought additional trials from other sources and by contacting study authors for unpublished data and trials. SELECTION CRITERIA: Randomised or quasi‐randomised controlled trials in women with symptomatic or urodynamic diagnosis of stress or mixed incontinence that included laparoscopic surgery as the intervention in at least one arm of the studies. DATA COLLECTION AND ANALYSIS: The review authors evaluated trials for methodological quality and their appropriateness for inclusion in the review. Two review authors extracted data and another cross checked them. Where appropriate, we calculated a summary statistic. MAIN RESULTS: We identified 22 eligible trials. Ten involved the comparison of laparoscopic with open colposuspension. Whilst the women's subjective impression of cure seemed similar for both procedures, in the short‐ and medium‐term follow‐up, there was some evidence of poorer results of laparoscopic colposuspension on objective outcomes. The results showed trends towards fewer perioperative complications, less postoperative pain and shorter hospital stay for laparoscopic compared with open colposuspension, however, laparoscopic colposuspension was more costly. Eight studies compared laparoscopic colposuspension with newer 'self‐fixing' vaginal slings. There were no significant differences in the reported short‐ and long‐term subjective cure rates of the two procedures but objective cure rates at 18 months favoured slings. We observed no significant differences for postoperative voiding dysfunction and perioperative complications. Laparoscopic colposuspension had a significantly longer operation time and hospital stay. We found significantly higher subjective and objective one‐year cure rates for women randomised to two paravaginal sutures compared with one suture in a single trial. Three studies compared sutures with mesh and staples for laparoscopic colposuspension and showed a trend towards favouring the use of sutures. AUTHORS' CONCLUSIONS: Currently available evidence suggests that laparoscopic colposuspension may be as good as open colposuspension at two years post surgery. However, the newer vaginal sling procedures appear to offer even greater benefits, better objective outcomes in the short term and similar subjective outcomes in the longer term. If laparoscopic colposuspension is performed, the use of two paravaginal sutures appears to be the most effective method. The place of laparoscopic colposuspension in clinical practice should become clearer when there are more data available describing long‐term results. A brief economic commentary (BEC) identified three studies suggesting that tension‐free vaginal tape (TVT) may be more cost‐effective compared with laparoscopic colposuspension but laparoscopic colposuspension may be slightly more cost‐effective when compared with open colposuspension after 24 months follow‐up.